Medications package inserts’ usefulness to doctors and patients: Sudanese doctors perspective - Idris, Kamal Addin Mohammad Ahmad; Yousif, Mirghani A.; Elkhawad, Abdalla O. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Written medication information is important for both doctors and patients. In the developing countries, the medication package inserts (PIs) represent the most available and easily accessible source of written medication information. The main objective of the present study was to assess the knowledge, attitude, and practice of Sudanese doctors toward written medication information in the PIs, and its usefulness for both doctors and patients. Methods: Four hundred (n=400) doctors were randomly selected and addressed with an open to answer the questionnaire composed of fifteen questions (n=15). Results: A big majority (95.7%) of the respondents considered the medications’ PIs, which they regularly read (93.2%), as a reliable and useful source of medication information in their prescribing. Only a minority of the respondent doctors (43.6%) used to advise their patients to read the PIs, whereas a majority (62.4%) of respondents believed that patients might find difficulty in understanding written medication information in the PI. The majority (61.3%) of respondent used to rely on pharmacists to provide patients with the needed medication information. The majority of the respondents (82.2%) used to inform their patients about the possible medication side effects. Respondents ranked medications’ dose (79.5%), how to use it (77.3%) and information about side effects (73%) on top of patients’ medication information most needed particulars. Conclusion: Doctors should give more attention to their patients’ medication information specific needs, advice and motivate them to read the PIs before using their medications.